Getting Smarter About Data and Access in Smart Cities - Patricia McKenna, H. (Universal Access in Human-Computer Interaction. Theory, Methods and Tools, 2019)
The purpose of this paper is to explore access in relation to new forms of urban data enabled by more aware people and aware technologies in smart cities. Focusing on the constructs of awareness, learning, openness, and engagement, a review of the research literature for data access and universal access in relation to smart cities is provided. As such, a theoretical space for data access is developed as a dimension of the construct of universal access. The research design for this work employs an exploratory case study approach, using multiple methods of data collection including interviews and survey in small to medium to large sized cities, mostly in Canada and extending to cities in other countries. Content analysis is used as an analytic technique for qualitative data to identify insights while descriptive statistics are used in the analysis of quantitative data. This work makes a contribution to: (a) the research literature for smart cities; (b) urban theory by advancing a conceptual framework for ambient access in learning, smart, and future cities; and (c) spaces for debate, inquiry, theorizing, and everyday interactions pertaining to urban data in smart cities, regions, and communities.